(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2020)
The study explains the creative process to compose an innovative scientific communication product: Interactive Multimedia Video Article. The result is a pilot product based on the IMRaD research format and represents an alternative to the traditional research article.